Investigation of Anxiety Levels Among Male U16 Volleyball Players at VOPAS Semarang - Sulfanjanti, Anggit Pramudya; Romadhoni, Wiga Nurlatifa (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2026)
This study aims to identify the anxiety levels of male U16 volleyball athletes at VOPAS Semarang. The study used a quantitative descriptive method involving 30 athletes through total sampling. Data collection was conducted using the Sport Anxiety Scale-2 (SAS-2) instrument, which consists of 15 statement items with a 4-point Likert scale. The data were analyzed using descriptive statistics, including minimum and maximum values, mean, standard deviation, frequency, and percentage to describe the general trend of the athletes' anxiety levels. The results showed that the anxiety scores ranged from 15.00 to 46.00, with a mean of 29.70 and a standard deviation of 9.41807. Based on categorization, 60% of athletes were at a moderate level of anxiety, 20% of athletes were in the low category, and 20% of athletes were in the high category. These findings indicate that most athletes experience moderate levels of anxiety with variations in responses between individuals within a team. The results of this study emphasize the importance of managing psychological aspects in the coaching process through the integration of mental training programs to support athletes' psychological readiness and stability in facing training and competition.